2008
DOI: 10.1093/rpd/ncn254
|View full text |Cite
|
Sign up to set email alerts
|

Childhood leukaemia near British nuclear installations: methodological issues and recent results

Abstract: In 2008, the German Childhood Cancer Registry published the results of the Kinderkrebs in der Umgebung von Kernkraftwerken (KiKK) study of childhood cancer and leukaemia around German nuclear power stations. The positive findings appeared to conflict with the results of a recent British analysis carried out by the Committee on Medical Aspects of Radiation in the Environment (COMARE), published in 2005. The present paper first describes the COMARE study, which was based on data from the National Registry of Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 5 publications
1
31
0
1
Order By: Relevance
“…28 A 2008 British study by Bithell et al was also designed in response to the KiKK study. 29 Comparable to the earlier German ecological studies, 9,10 it found "no evidence that acute leukaemia in children < 5 years has a higher incidence close to nuclear power stations in Britain." However, the authors conceded that the 95% confidence intervals in their study are so wide that the difference with the data reported in the KiKK study "is only marginally statistically significant."…”
Section: Consistency With Other Studiesmentioning
confidence: 75%
See 1 more Smart Citation
“…28 A 2008 British study by Bithell et al was also designed in response to the KiKK study. 29 Comparable to the earlier German ecological studies, 9,10 it found "no evidence that acute leukaemia in children < 5 years has a higher incidence close to nuclear power stations in Britain." However, the authors conceded that the 95% confidence intervals in their study are so wide that the difference with the data reported in the KiKK study "is only marginally statistically significant."…”
Section: Consistency With Other Studiesmentioning
confidence: 75%
“…However, the authors conceded that the 95% confidence intervals in their study are so wide that the difference with the data reported in the KiKK study "is only marginally statistically significant." 29 The words "no evidence" in the conclusions of the papers by Evrard et al 27 and Bithell et al, 29 as well as Laurier et al's statement that their data "do not indicate an excess risk," are often misleadingly interpreted as negative rather than as inconclusive findings. These interpretations ignore a fundamental rule in epidemiology: Absence of evidence of an effect does not constitute evidence of absence of that effect.…”
Section: Consistency With Other Studiesmentioning
confidence: 99%
“…The authors indicated that, according to current radiobiological theory, this excess risk is not to be expected, in view of the low levels of exposure to artificial radiation proceeding from the installations. Efforts have, since, been made to replicate these results in the UK (Bithell et al 2008), France (Laurier et al 2008) and, more recently, in a cohort study in Switzerland (Spycher et al 2011), without statistically significant excess risk being found. In this respect, it is estimated that exposure to radioactive effluents from facilities currently in service is several orders of magnitude below the limit values set by regulatory requirements (in Spain 0.1 mSv/year at NPPs and 0.3 mSv/year at all remaining nuclear installations).…”
Section: Introductionmentioning
confidence: 89%
“…Not surprisingly, therefore, taking account of these covariables and using data from the early days of operation of the plant, Enstrom (1983) found that childhood leukemia is no more prevalent around San Onofre than elsewhere. However, removing San Onofre from the Greiser (2009) data set, and adding some studies he has overlooked (for instance Bithell et al (2008) and Kaatsch et al (2008b)) the initial surplus of leukemia cases among children aged 0-4 turns into a deficit (table 4): Other than in table 2, the data for the UK now comprises all sorts of acute leukemia as specified by International Classification of Childhood Cancer Groups 11 and 12; therefore, incidence is lager. The data from Germany was collected by almost the same research group which had supplied the German data for table 2 (Kaatsch et al 2008a), but covers a longer time span.…”
Section: Disregard Of Confounding Factorsmentioning
confidence: 99%